Fully discrete high-order TVD schemes for a scalar hyperbolic conservation law - Shi, Jian; Toro, E. F. (Cranfield University, 1993)
In this paper we investigate fully discrete high-order TVD schemes for a scalar hyper- bolic conservation law using flux limiters . Formulae which define Courant number dependent TVD regions for second and third-order TVD schemes are established. A semi-empirical TVD procedure for an m-th order scheme (m ≥ 4) are proposed and tested.